Stacking faults in SiCf/SiC composite obtained by chemical vapor reaction process - Florian, Marcio; Marques, Rodrigo Fernando Costa [UNESP]; Carvalho, Luiz Eduardo; Cairo, Carlos Alberto Alves; Barelli, Nilso [UNESP] (Trans Tech Publications, 2008)
SiC fiber-reinforced SiC matrix composite (SiCf/SiC) is one of the leading candidates in ceramic materials for engineering applications due to its unique combination of properties such as high thermal conductivity, high resistance to corrosion and working conditions. Fiber-reinforced composites are materials which exhibit a significant improvement in properties like ductility in comparison to the monolithic SiC ceramic. The SiCf/SiC composite was obtained from a C/C composite precursor using convertion reaction under high temperature and controlled atmosphere. In this work, SiC phase presented the stacking faults in the structure, being not possible to calculate the unit cell size, symmetry and bond lengths but it seem equal card number 29-1129 of JCPDS.
Keywords: Convertion reactions; SiCf/SiC composite; Stacking faults; X ray analysys; C/c composites; Chemical vapor reaction processes; Controlled atmospheres; Engineering applications; Fiber-reinforced composites; High resistances; High temperatures; Reaction under; Sic ceramics; SiC fibers; Sic matrix composites; Unit cell sizes; Working conditions; Carbon fiber reinforced plastics; Ceramic materials; Chemical properties; Corrosion resistance; Fiber reinforced materials; Materials properties; Metallic matrix composites; Powders; Silicon carbide; Carbon Fibers; Ceramics; Chemical Properties; Chemical Reactions; Composites; Conversion; Materials Handling; Powder; Reinforced Plastic; Reinforcement; Silicon Carbide; Stacking; Thermal Conductivity; X Ray Analysis